2011
DOI: 10.1126/science.1201662
|View full text |Cite
|
Sign up to set email alerts
|

The Leukemogenicity of AML1-ETO Is Dependent on Site-Specific Lysine Acetylation

Abstract: The chromosomal translocations found in acute myelogenous leukemia (AML) generate oncogenic fusion transcription factors with aberrant transcriptional regulatory properties. Although therapeutic targeting of most leukemia fusion proteins remains elusive, the posttranslational modifications that control their function could be targetable. We found that AML1-ETO, the fusion protein generated by the t(8;21) translocation, is acetylated by the transcriptional coactivator p300 in leukemia cells isolated from t(8;21… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
232
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 214 publications
(241 citation statements)
references
References 29 publications
9
232
0
Order By: Relevance
“…The significance of this observation to this study is that RUNX1 is an important upstream activator of the SPI1 gene in humans and the Sfpi1 gene in mice (56). PU.1 levels are reduced upon expression of RUNX1 fusion proteins such as ETO-RUNX1 (57,58). Recently, it was also shown that B-ALL cells harboring ETV6-RUNX1 fusions express reduced levels of Spi-B (14).…”
Section: Discussionmentioning
confidence: 88%
“…The significance of this observation to this study is that RUNX1 is an important upstream activator of the SPI1 gene in humans and the Sfpi1 gene in mice (56). PU.1 levels are reduced upon expression of RUNX1 fusion proteins such as ETO-RUNX1 (57,58). Recently, it was also shown that B-ALL cells harboring ETV6-RUNX1 fusions express reduced levels of Spi-B (14).…”
Section: Discussionmentioning
confidence: 88%
“…9,10 AML1-ETO was shown to activate expression of BCL-2 and p21, possibly via interacting with p300. [11][12][13] AML1-ETO promotes stem cell renewal and blocks hematopoietic differentiation. [14][15][16] However, its role in blocking cell-cycle progression and promoting apoptosis contradicts its function in promoting leukemogenesis and therefore requires secondary mutagenic events for full transformation.…”
Section: Introductionmentioning
confidence: 99%
“…6 Furthermore, C646 can selectively induce cell death in leukemia cells containing the AML-ETO gene fusion, which encodes a transcription factor whose activity is dependent on p300/CBP KAT function. 7,8 Recently there has been an increased interest in understanding the mechanisms and liabilities of pan-assay interference compounds (commonly referred to as PAINS).…”
mentioning
confidence: 99%